What is the function of Matrix Metalloproteinase-2 and Matrix Metalloproteinase-9 in pain processes? - Hamdi, Tasrif (Journal of Society Medicine, 2023)
At the cellular level, the pathophysiology of neuropathic pain can be divided into two parts. The first is the early phase (several days) and the second is the late phase (ranging from weeks to months and years). Cancer cell growth in the periphery will cause nerve damage in the periphery and prolonged pain will cause changes in nerve transmission processes in the periphery and centre. This underlies the occurrence of peripheral neuropathic pain. Damage to peripheral nerve tissue will trigger peripheral sensitisation and then central sensitisation. After peripheral nerve cell damage (including axon damage), schwan cells will release MMP-9, initiating macrophage cell infiltration. Then there will be degradation of myelin basic protein. The presence of damaged axons will cause an increase in the number of sodium channels and hyperexcitability of ectopic signals from afferent nerve fibres. The result is a continuous action potential that eventually contributes to central sensitisation characterised by hyperalgesia and allodynia. This review summarizes that neuropathic pain occurs through hyperexcitability (hypersensitisation) of nerve cells is IL-1β, MMP-9 in the early phase, MMP-2 in the late phase and finally microglia and astrocyte cells.